the Membangun Citra UMKM Kuliner Lewat Desain: Studi Visual pada Media Promosi Oishii Kebab - betri, betri indriani; Ayu Lestari; Tiara Amanda Putri (CV. ITTC INDONESIA, 2025)
Visual communication plays an important role for MSMEs because it functions as the main tool in building and strengthening business branding. With good visual communication design, MSMEs can convey brand values ​​and messages effectively and easily remembered by consumers, thereby increasing competitiveness and attracting more customers. Visual elements such as logos, packaging, and consistent promotional materials help create a strong visual identity, which is a distinctive marker of MSME products in an increasingly competitive market. In addition, visual communication is also very important in the context of digital branding, especially through social media and e-commerce platforms. Visual works such as product photos and video tutorials not only display product quality, but also strengthen brand image and attract the attention of consumers more widely. This greatly helps MSMEs in increasing brand awareness and building customer loyalty in the digital era. Thus, mastering visual communication is a strategic key for MSMEs to expand the market, increase interaction with consumers, and encourage sustainable business growth